2006
DOI: 10.1111/j.1440-1843.2005.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal responsiveness to both isoprenaline and beta2‐adrenoreceptor blockade by propranolol in cigarette smoke exposed and sensitized guinea pigs

Abstract: The results of this study indicate an increased tracheal response to a beta(2)-adrenergic stimulating drug and enhanced beta(2)-adrenergic blockade by propranolol in both AECS and AECS + sensitized. These results suggest similar increase in airway responsiveness to beta(2)-adrenergic agonists and beta(2)-receptor blockade in AECS and AECS + sensitized guinea pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…Tracheal chains of Dunkin-Hartley guinea pigs were prepared as previously described [23] and suspended in a 10 ml organ bath (organ bath 61300, Bio Science Palmer-Washington, Sheerness, Kent, UK) containing Krebs-Henseleit solution with known composition [23] which was maintained at 37° and gassed with 95% O 2 and 5% CO 2 .…”
Section: Animals and Tissue Preparationsmentioning
confidence: 99%
“…Tracheal chains of Dunkin-Hartley guinea pigs were prepared as previously described [23] and suspended in a 10 ml organ bath (organ bath 61300, Bio Science Palmer-Washington, Sheerness, Kent, UK) containing Krebs-Henseleit solution with known composition [23] which was maintained at 37° and gassed with 95% O 2 and 5% CO 2 .…”
Section: Animals and Tissue Preparationsmentioning
confidence: 99%
“…It gets accumulated in embryonic organs such as kidney (2). Cigarette smoke increased upper airway tracts sensitivity to isoprenaline (3). Furthermore, nicotine exposure in the embryonic period resulted in decreased fibronectin expression in pulmonary parenchyma (4).…”
Section: Introductionmentioning
confidence: 99%
“…[12] This hypothesis was then tested with another β-agonist (salbutamol) in asthmatic patients and also in smokers. [13,14] This phenomenon was also demonstrated in tracheal chains of sensitized and COPD animals [30,31] as well as epithelial denuded trachea. [32] In most of the above-mentioned studies a close correlation was found between airway responsiveness to methacholine and β-agonist.…”
Section: Discussionmentioning
confidence: 94%